Neuro-developmental status of children with congenital hypothyroidism: experience in a tertiary hospital of Bangladesh - Islam, Nasreen; Kabir, Sayeeda; Mohsin, Fauzia; Mahbuba, Sharmin; Zabeen, Bedowra; Baki, Abdul; Nahar, Jebun (BIRDEM Medical Journal, 2020)
Background: Congenital hypothyroidism is one of the most common preventable causes of mental retardation. Early diagnosis and initiation of treatment is fundamental for optimal neuro-developmental outcome in children with congenital hypothyroidism. Thyroid hormones play crucial role in early neuro-development especially in the first 2-3 years of life. If left untreated or delayed initiation of treatment in congenital hypothyroidism results in neurological and psychological deficits. Aim of this study was to assess neuro-developmental status of children with congenital hypothyroidism who were on treatment (levo-thyroxine) started at different ages. Methods: This cross-sectional study was done at paediatric endocrine outpatient department (OPD) and child development centre (CDC), BIRDEM General Hospital. Children with congenital hypothyroidism presenting at different ages who were followed up at pediatric endocrine OPD between January 2014 and January 2015 were included in the study.Their functional status in different domains were studied by rapid neuro-developmental assessment (RNDA) in CDC. Children with Down syndrome and perinatal asphyxia were excluded. Results: Neuro-developmental assessment was done in 34 children (male 21, female 13). Mean age during assessment was 36 months (standard deviation 18.56). Eighteen patients (53%) were diagnosed in BIRDEM General Hospital and rest 16 (47%) were diagnosed outside BIRDEM General Hospital. Patients were grouped into 4 on the basis of age of diagnosis and start of treatment: group I (age 0-1 month), n=6 (18%); group II (age >1-3 months), n=7 (21%); group III (age >3-12 months), n=9 (26%); group IV (age >12months), n=12 (35%). In group I, five (84%) had normal development and one had mild delay in cognition. In group II, three (43%) had normal development. Cognition and behavior was delayed in 3 patients (43% each), followed by delay in speech in 2 (29%). All patients (100%) in group III and IV had developmental delay, predominant domains affected were speech, cognition and behavior. Conclusion: We have found developmental delay especially in the domain of speech, cognition and behavior in children with congenital hypothyroidism who have started levo-thyroxin late. Early diagnosis and initiation of treatment is fundamental for optimal neuro-developmental outcome in children with congenital hypothyroidism. Birdem Med J 2021; 11(1): 63-66